Teorija črpanja posod oz. sistemov in opredelitev velikosti puščanja - Nemanič, Vincenc (Vakuumist, 1997)
High vacuum and ultra high vacuum technology depends crucially on tightness of vessels and components. The most sensitive methods developed to control and measure leakage were so called vacuum methods, where leakage is measured in evacuated vessel. Nowadays, high demands for tightness, comparable to those in high vacuum technique, are met in several other fields. In the paper, basic quantities and relations, necessary to describe pump-down process are described. Physical units for measuring leakage rates, which are closely related to difficulty range of particular application, are also introduced.
Keywords: vakuumska tehnika; tesnjenje; netesnost; črpanje; dinamični sistemi; statični sistemi